2007
DOI: 10.1039/b704235c
|View full text |Cite
|
Sign up to set email alerts
|

Response to ALA-based PDT in an immortalised normal breast cell line and its counterpart transformed with the Ras oncogene

Abstract: Aminolevulinic acid (ALA)-based photodynamic therapy (PDT) has been successfully employed in the treatment of certain tumours. Porphyrins endogenously generated from ALA induce tumour regression after illumination with light of an appropriate wavelength. The aim of this work was to compare porphyrin production from ALA and sensitivity to photodynamic treatment in a tumour/normal cell line pair. We employed the HB4a cell line from normal mammary luminal epithelium and its counterpart transfected with the oncoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
(17 reference statements)
1
9
0
Order By: Relevance
“…However, it is more resistant to PDT, particularly when low prophotosensitizer concentrations are used. This feature has been previously observed by our group for the mammary cell line pair HB4a and HB4a-Ras (48), showing that overexpression of RAS oncogene confers resistance to ALA-PDT, independent of the amount of porphyrins synthesized. We were therefore intrigued to explore the effectiveness of prodrugs that are proven to perform significantly better than ALA in normal cell lines in this clinically relevant oncogenic system.…”
Section: Discussionsupporting
confidence: 59%
“…However, it is more resistant to PDT, particularly when low prophotosensitizer concentrations are used. This feature has been previously observed by our group for the mammary cell line pair HB4a and HB4a-Ras (48), showing that overexpression of RAS oncogene confers resistance to ALA-PDT, independent of the amount of porphyrins synthesized. We were therefore intrigued to explore the effectiveness of prodrugs that are proven to perform significantly better than ALA in normal cell lines in this clinically relevant oncogenic system.…”
Section: Discussionsupporting
confidence: 59%
“…16,23,29 Only one other in vitro study has compared PpIX production in a breast cancer and corresponding normal cell line. Specifically, Rodriguez et al 29 showed that HB4-A R-ras breast cancer cell lines had higher PpIX fluorescence compared to immortalized cells not transfected with the Ras oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…43 Previous studies illustrate that ALA-induced PpIX has the capability to differentially detect breast cancer in multiple biological model systems. 18,20,29,30,36,40 Fluorescence quantification of PpIX in breast cancer cell lysates treated with ALA was higher as compared to patient-matched normal cell lysates treated with ALA in explanted cell cultures from five breast cancer patients. 28 Studies on an in vivo animal model have shown that ALA-induced fluorescence can be used to enhance early detection of neoplastic and metastatic tissue from normal tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that Ras oncogene confers resistance to ALA-PDT [106] as well as PDT with other PS such as PII, merocyanine 540 (MC540), BPD-MA, acridine orange and m-THPC [107] (Fig. 6).…”
Section: Dna Alterations and Gene Expressionmentioning
confidence: 99%